Independent Futures : Creating User-Led Disability Services in a Disabling Society. - Barnes, Professor Colin (Policy Press, 2006)
The number of disability related support services controlled and run by disabled people themselves has increased significantly in the UK and internationally over the past forty years. As a result, greater user involvement in service provision and delivery is a key priority for many western Governments. This book provides the first comprehensive review and analysis of these developments in the UK.